Estimates of Some Operators on One-Sided Weighted Morrey Spaces - Shaoguang Shi; Zunwei Fu (Abstract and Applied Analysis)
A version of one-sided weighted Morrey space is introduced. The boundedness of some classical one-sided operators in harmonic analysis and PDE on these spaces are discussed, including the Riemann-Liouville fractional integral.